Improvement of removal rate of tape lapping by applying fluid with ultrasonic excited cavitation - Isobe, Hiromi (Fuji Technology Press, 2021)
Lapping with a lapping tape refers to a finishing process in which a new tape is continuously supplied to its processing area and pressed down with a pressure roller during its relative motions. In response to the growing demand for lapping high-hardness materials with high efficiency, lapping tapes with superabrasive grains formed in a textured structure with a bond have been recently utilized. In this study, we supply a working fluid that has passed through the slit between ultrasonically oscillating blades to processing points. Variations of sound pressure generate cavitation in the working fluid. Impulse waves due to the collapse of cavitation bubbles inhibit chips from getting adhered to the chip pockets of the lapping tape. We have lapped hardened SUJ2 with plural lapping tapes of different characteristics. In lapping with a lapping tape using diamond abrasive grains, we have improved the time constant for the changes in surface roughness in relation to the lapping time from 18.9 s to 7.6 s by superimposing ultrasonic oscillations, consequently, the lapping speed improved. We have compared the effects of ultrasonic oscillations for three types of lapping tapes and discovered that fewer abrasive grains and lower chip adhesion firmness due to the abrasive grains formed in a textured structure increased the effects of ultrasonic oscillations.